Rotaxanes as Cages to Control DNA Binding, Cytotoxicity, and Cellular Uptake of a Small Molecule - Kench,T; Summers,PA; Kuimova,MK; Lewis,JEM; Vilar,R (Angewandte Chemie, 2021)
Abstract The efficacy of many drugs can be limited by undesirable properties, such as poor aqueous solubility, low bioavailability, and “offtarget” interactions. To combat this, various drug carriers have been investigated to enhance the pharmacological profile of therapeutic agents. In this work, we demonstrate the use of mechanical protection to “cage” a DNAtargeting metallodrug within a photodegradable rotaxane. More specifically, we report the synthesis of rotaxanes incorporating as a stoppering unit a known Gquadruplex DNA binder, namely a Pt II salphen complex. This compound cannot interact with DNA when it is part of the mechanically interlocked assembly. The second rotaxane stopper can be cleaved by either light or an esterase, releasing the Pt II salphen complex. This system shows enhanced cell permeability and limited cytotoxicity within osteosarcoma cells compared to the free drug. Light activation leads to a dramatic increase in cytotoxicity, arising from the translocation of Pt II salphen to the nucleus and its binding to DNA.